TAFSIR AYAT-AYAT AL-QUR’AN TENTANG FUNGSI MANAJEMEN PENDIDIKAN (Studi Tafsir Maudhu’i dalam QS. Al-Hasyr : 18, QS. Ali-Imran : 103, QS. Al-Kahfi : 2, dan QS. Al-Infhithar : 10-12) - Fahri Sahrul Ramadhan; Ahmad Saeful Hidayat (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2024)
The management function is one thing that cannot be separated from the management process itself. Apart from being basic and inherent, the management function also becomes a reference for a manager in achieving the desired goals. In the Islamic view, the function of education management reviewed in the Al-Qur'an has several discussions including: (1) Planning; which is the initial function of management activities in achieving goals effectively and efficiently, (2) Organizing; or a system of cooperation between a group of people to achieve a common goal, (3) Actuating; as a whole process of providing work encouragement, (4) Supervision (Controlling); as a management function to ensure that activities in the organization are as planned. This article aims to reveal the meaning in the interpretation of the verses of the Qur'an relating to the management function in QS. Al-Hasyr: 18, QS. Ali-Imran: 103, QS. Al-Kahf: 2, and QS. Al-Infithar: 10-12 and the relevance of theories and their interpretations. This research is library research and is included in the descriptive qualitative research approach. The interpretation method used is the thematic interpretation method or more popularly known as Tafsir Maudhu'i.